2020
DOI: 10.1017/s2045796020000529
|View full text |Cite
|
Sign up to set email alerts
|

Does physical ill-health increase the risk of suicide? A census-based follow-up study of over 1 million people

Abstract: Abstract Aims Mental ill-health is a known risk factor for suicide mortality. However, the relationship between physical ill-health and suicide is less clear. This study examined the relationship between different aspects of physical ill-health and the risk of suicide death. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…We were unable to demonstrate the association between suicidal behaviour and having chronic medical illness because this study did not take into account the severity and types of the chronic medical illness. Another explanation was that a previous study showed the effect that medical illness has on a person’s life in terms of disruption to daily activity rather than the number of medical conditions that predict suicide risk ( 28 ), which could explain the lack of association in our study.…”
Section: Discussionmentioning
confidence: 59%
“…We were unable to demonstrate the association between suicidal behaviour and having chronic medical illness because this study did not take into account the severity and types of the chronic medical illness. Another explanation was that a previous study showed the effect that medical illness has on a person’s life in terms of disruption to daily activity rather than the number of medical conditions that predict suicide risk ( 28 ), which could explain the lack of association in our study.…”
Section: Discussionmentioning
confidence: 59%
“…Many chronic illnesses lead to reduction in daily activities; ME/CFS stipulates such a reduction as a criterion for diagnosis [4]. In a recent census-based study of people with chronic physical illnesses in Northern Ireland, the degree of functional limitation in chronic illness was the largest statistical predictor of death by suicide [25]. Those who reported that their day-to-day activities were "limited a lot" were more than three times as likely to die by suicide as those without functional limitations.…”
Section: Risk Factors For Suicidementioning
confidence: 99%
“…Another Census item asked “Are your day-to-day activities limited because of a health problem or disability which has lasted, or is expected to last at least 12 months?” with responses, no; yes-limited a little; yes-limited a lot. Suicide is common in those with comorbid multiple physical health conditions and limitations of daily activities ( Almeida et al, 2016 ; Onyeka et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%